2021
DOI: 10.1186/s12889-021-10896-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between the social isolation and depressive symptoms after the great East Japan earthquake: findings from the baseline survey of the TMM CommCohort study

Abstract: Background Social isolation and mental health issues have become a severe problem in disaster areas in the Great East Japan Earthquake. This study examined whether the combination of the house damage and social isolation or the combination of the death of family members and social isolation is associated with depressive symptoms among survivors using the baseline study data of the Tohoku Medical Megabank Project Community-Based Cohort Study (TMM CommCohort Study). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Lockdown has also been associated with an increase in family violence ( Campbell, 2020 ; Gadermann et al, 2021 ), economic hardship ( Fegert et al, 2020 ); increased alcohol consumption ( Gadermann et al, 2021 ); a decrease in exercise ( Deschasaux-Tanguy et al, 2021 ); and a global sense of loss and grief ( de Jong et al, 2020 ). These findings are consistent with studies conducted during the SARS pandemic ( Blendon et al, 2004 ) and natural disasters ( Cao et al, 2013 ; Pujadas Botey and Kulig, 2014 ; Kotozaki et al, 2021 ; O’Donohue et al, 2021 ), suggesting a relationship between social isolation and poor social, mental, and physical health outcomes.…”
Section: Introductionsupporting
confidence: 90%
“…Lockdown has also been associated with an increase in family violence ( Campbell, 2020 ; Gadermann et al, 2021 ), economic hardship ( Fegert et al, 2020 ); increased alcohol consumption ( Gadermann et al, 2021 ); a decrease in exercise ( Deschasaux-Tanguy et al, 2021 ); and a global sense of loss and grief ( de Jong et al, 2020 ). These findings are consistent with studies conducted during the SARS pandemic ( Blendon et al, 2004 ) and natural disasters ( Cao et al, 2013 ; Pujadas Botey and Kulig, 2014 ; Kotozaki et al, 2021 ; O’Donohue et al, 2021 ), suggesting a relationship between social isolation and poor social, mental, and physical health outcomes.…”
Section: Introductionsupporting
confidence: 90%
“…Social networks and social capital have been investigated with regard to health and social relationships among earthquake survivors. Two years after the GEJE, social isolation measured using the Lubben Social Network Scale 6 was significantly associated with depressive symptoms evaluated using the Center for Epidemiological Studies-Depressive Scale [ 47 ]. Among survivors of the GEJE, those who considered community trust weak in 2011 had significantly higher Athens Insomnia Scale scores, a measure of sleep disturbance, for the entire period up to 2017 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 The data suggested that a combination of social isolation and severe house damage, alongside the death of family members, was associated with a higher risk of depressive symptoms, although the interaction was not statistically significant. 19 In addition to the above cohorts, ToMMo conducted a cross-sectional study from 2012 to 2015 to investigate and address the health needs of school children affected by this disaster, providing follow-up support to the cases in need. 20 The study found factors associated with children's health in post-disaster settings, for example, a significant association between the severity of eczema and mental health problems.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%